Efficient Certificateless Anonymous Multi-Receiver Encryption Scheme without Bilinear Parings. (24th July 2018) - Gao, Ronghai; Zeng, Jiwen; Deng, Lunzhi
Abstract : With the growing development of Internet technology and popularization of mobile devices, we easily access the Internet anytime and anywhere by mobile devices. It has brought great convenience for our lives. But it brought more challenges than traditional wired communication, such as confidentiality and privacy. In order to improve security and privacy protection in using mobile network, numerous multi-receiver identity-based encryption schemes have been proposed with bilinear pairing and probabilistic hap-to-point (HTP) function. To address the troubles of private key escrow in multi-receiver encryption scheme based on ID-PKC, recently, some certificateless anonymous multi-receiver encryption (CLAMRE) schemes are introduced. But previous CLAMRE schemes using the bilinear pairing are not suitable to mobile device because the use of bilinear pairing and probabilistic hash-to-point (HTP) function results in expensive operation costs in encryption or decryption. In this paper, we propose an efficient CLAMRE scheme using elliptic curve cryptography (ECC) without bilinear pairing and HTP hash function. Since our scheme does not use bilinear pairing and HTP operation during the encryption and decryption process, the proposed CLAMRE scheme has much less computation cost than the latest CLAMRE schemes. Performance analysis shows that runtime of our scheme is much less when the sender generates ciphertext, compared with existing schemes. Security analysis shows proposed CLAMRE scheme provides confidentiality of message and receiver anonymity under the random oracle model with the difficulties of decision Diffie-Hellman problem and against the adversaries defined in CL-PKC system.